HISTOPATHOLOGY OF COLLECTOTRICHUM GLOESPORIOIDES IN INFECTED MANGO ((MANGIFERA INDICA L.) FRUITS - oladele, oluwole (Journal of Agricultural Sciences (Belgrade), 2020)
The mango (Mangifera indica L.) is an appealing tropical fruit with pleasant flavor and taste, high nutritional value and beneficial medicinal properties. However, postharvest losses due to Colletotrichum gloeosporioides (Penz and Sacc.) causing anthracnose remain a serious threat to mango producers. Hence, histopathology of mango fruits ((Mangifera indica L.) after artificially infected by Colletotrichum gloeosporioides ((Penz. and Sacc.) was investigated. Fruits at the physiologically mature stage were wounded (cut) in the peels and thereafter inoculated with spore suspension of Colletotrichum gloeosporioides (8.04 x 103 conidia m1-1) and later incubated at 28±2ºC for 5 days to allow pathogen establishment. The infected peel was then carefully cut with a new razor blade and dehydrated in series in different grades (50, 70, 80, 90 and 100%) of ethyl alcohol for 1½ hours each. Histopathological studies were thereafter carried out on the infected peel tissue excised from inoculated fruits using standard procedures while unwounded peels of fruits that were not artificially infected served as control and sections were examined by light microscopy to observe histopathological differences between the infected and non-infected fruits. Results from this study revealed that only the wounded peel showed symptoms of anthracnose infection as a result of the artificial inoculation but the unwounded peel showed no disease symptoms. This showed that the fungus infected the mango fruits through the peel wounds. Besides, disorganization of the cells and rupture of the cell walls were observed microscopically and thus indicating disease establishment in the infected fruits. Therefore, the potential of the fungus to infect through wounds suggests that mango growers should improve the traditional harvesting methods and avoid bruises during harvesting.